The relationship between strategic information systems and strategic performance: The case of Islamic banks in Malaysia - Ahmad Shukri, Yazid; Farouk Umar, K (2017)
The banking business is very competitive and requires good strategies,thus,the use of information systems in the daily operation of banks is considered critical. This paper is aimed at determining the effects of strategic information systems on the strategic performance of Islamic banks. The sample of the study population was randomly selected and a total of 302 questionnaires were distributed among Islamic bank executives in Kuala Terengganu, Malaysia. The analysis was conducted using a second generation multivariate analysis,also known as Structural Equation Modelling (SEM). The results of the study reveal that strategic information systems have a positive effect on the strategic performance of Islamic banks,especially in terms of flexibility and cost reduction. This paper reveals that Islamic bank executives and stakeholders are obliged to fully comprehend the relevance of strategic information systems in enhancing strategic performances of organisations.